Priority 1: Sustainable management of natural resources - Zdruli P.; Lamaddalena N.; Todorovic M.; Scardigno A.; Calabrese J.; Ladisa G.; Verrastro V.; Pereira L.S.; Coppola A.; Marino M. (Feeding knowledge, 2017)
The Priority 1 of the Feeding Knowledge project describes the links between natural resources status and management and their inter-linkages with food security by analysing five important components that include land, water, climate change, biodiversity, and energy. Natural resource degradation is not a fate but often receive a “back seat” position in the Governmental agendas. It can be reversed however, if it is caught up early and there is a political will to stop it. Research results show that there are many options available for its recovery through sustainable land and water management, biodiversity conservation, efficient use of energy sources and mitigation/adaptation actions to climate change.
Expo Milano 2015